2018
DOI: 10.1159/000491983
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Rotenoid Deguelin Ameliorates Diabetic Neuropathy by Decreasing Oxidative Stress and Plasma Glucose Levels in Rats via the Nrf2 Signalling Pathway

Abstract: Background/Aims: Deguelin is a natural rotenoid that shows anti-inflammatory and antimicrobial activities. Rotenoids prevent oxidative damage and potentiate natural antioxidant activity in diabetic conditions, suggesting utility in treating diabetes and its complications. Here, we evaluate the potential efficacy of deguelin against diabetic neuropathy (DN). Methods: DN was induced by streptozotocin followed by daily treatment with deguelin (4, 6 or 8 mg/kg) for 14 days. Blood glucose was measured, neurobehavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…However, if oxidative stress persistently exists, the inflammation will cause the progressive tissue damage. Recent findings showed that Morin and natural rotenoid deguelin exerted neuroprotection in experimental diabetic neuropathy through antioxidative stress and antineuroinflammation [7,25]. Thus, targeting the cellular oxidative stress and inflammation pathway will be likely important therapeutic approaches in the future to reduce the incidence of diabetic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…However, if oxidative stress persistently exists, the inflammation will cause the progressive tissue damage. Recent findings showed that Morin and natural rotenoid deguelin exerted neuroprotection in experimental diabetic neuropathy through antioxidative stress and antineuroinflammation [7,25]. Thus, targeting the cellular oxidative stress and inflammation pathway will be likely important therapeutic approaches in the future to reduce the incidence of diabetic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the neuroprotective effect of nesfatin-1 in PD was further confirmed through in vivo and in vitro experiments, which showed that the antiapoptotic C-Raf-extracellular signal-regulated protein kinase 1/2 (ERK1/2) signaling pathway mediates the protective effect of nesfatin-1 on dopaminergic neurons against 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)induced neurotoxicity in C57BL/6 mice and 1-methyl-4-phenylpyridillium ion (MPP + )-induced cytotoxicity in MES23.5 cells. 45 Diabetic neuropathy (DN), one of the most debilitating outcomes of diabetes mellitus, is thought to be the consequence of oxidative stress, 46 inflammation, 47 and neural apoptosis. 48 More specifically, increased glucose levels damage the mitochondrial membrane and respiratory chain, resulting in the production of large amounts of ROS, 49 which accelerate the damage of lipids, proteins, and nucleic acids, and eventually lead to inflammation and neural apoptosis.…”
Section: Brain-related Diseasesmentioning
confidence: 99%
“…Diabetic neuropathy (DN), one of the most debilitating outcomes of diabetes mellitus, is thought to be the consequence of oxidative stress, 46 inflammation, 47 and neural apoptosis. 48 More specifically, increased glucose levels damage the mitochondrial membrane and respiratory chain, resulting in the production of large amounts of ROS, 49 which accelerate the damage of lipids, proteins, and nucleic acids, and eventually lead to inflammation and neural apoptosis.…”
Section: Antioxidant Anti-inflammatory and Anti-apoptotic Activitiementioning
confidence: 99%
“…Catechin, in a model of STZ-diabetic induced rats, was able to reduce the neuronal damage by increasing SOD and CAT, and reducing MDA and lymphocyte infiltration in nerve tissues [93]. Deguelin also ameliorates diabetic neuropathy, attenuated oxidative stress and neuroinflammation through the activation of NRF2 pathway, and partially restored the conduction velocities of neurons in diabetic rats by increasing (Na + -K + ) ATPase activity [94]. A similar neuroprotective effect against oxidative stress and inflammation was reported for phloretin, which either alone or in combination with the anti-neuropathic agent duloxetine promoted nerve fiber regeneration in STZ-induced diabetic rats [95].…”
Section: Diabetic Neuropathymentioning
confidence: 96%